A study for on‐demand generation regulation control. Issue 3 (25th September 2018) - Zoka, Yoshifumi; Koshimoto, Keita; Muraoka, Masaki; Kuwada, Yasunori; Mashima, Yuki; Rehiara, Adelhard Beni; Sasaki, Yutaka; Yorino, Naoto
Abstract: This paper proposes a real‐time generation regulation system named as "on‐demand generation regulation control" system, which is suitable for small independent power grids with unstable renewable energy generators. It has been developed as a part of "robust demand and supply control manager" and plays an important role of flexible frequency control that includes vehicle to grid and generation restriction when necessary. The main feature of the system is the integrated framework to effectively deal with hard‐to‐predict control options in a flexible way by observing the unstable generator outputs and all generators/batteries status including electric vehicles. In addition, a feedback system is also proposed to flexibly adjust the regulation capacity in case unexpected disturbances occur. The performance of the proposed system is verified through numerical simulations based on an actual test site with successful results.